Glucose-Regulated Protein 78-Induced Myeloid Antigen-Presenting Cells Maintained Tolerogenic Signature upon LPS Stimulation - Yang, Muyang; Zhang, Fan; Qin, Kai; Wu, Min; Li, Heli; Zhu, Huifen; Ning, Qin; Lei, Ping; Shen, Guanxin (Frontiers in Immunology, 2016)
The 78 kDa glucose-regulated protein (Grp78) is stress-inducible chaperone that mostly reside in the endoplasmic reticulum. Grp78 has been described to be released at times of cellular stress and as having extracellular properties that are anti-inflammatoryor favor the resolution of inflammation. As dendritic cells play a critical rolein both the priming of adaptive immune responses and the induction of self-tolerance, herein, we investigated the effect of Grp78 on the maturation of murine bone marrow derived dendritic cells (BMDCs). Results showed that BMDCs could be bound by AF488 labeled Grp78 and that Grp78 treatment induced a tolerogenic DC phenotype comparable to immature DCs. Furthermore, when exposed to LPS, Grp78 treated DC (DCGrp78) did not adopt a mature DC phenotype. DCGrp78-primed T cells exhibited reduced proliferation along with a concomitant expansion of CD4+CD25+FoxP3+ cells in PLNs and induction of T cell apoptosis in vitro and ex vivo. The above work suggests that Grp78 is an immunomodulatory molecule that could aid resolution of inflammation. It may thus contribute to induce durable tolerance to be of potential therapeutic benefit in transplanted allogeneic grafts and autoimmune diseases such as typeⅠdiabetes.